An investigation of the role the donor moiety plays in modulating the efficiency of 'donor-π-acceptor-π-acceptor' organic DSSCs. Issue 8 (23rd February 2017) - Park, Kwang-Won; Serrano, Luis A.; Ahn, Sungwoo; Baek, Myung Hoon; Wiles, Alan A.; Cooke, Graeme; Hong, Jongin
Abstract: Three 'D-π-A-π-A' based dyes have been synthesized featuring MeO-, MeS- and Me2 N- as donor residues and benzothiadiazole and cyanoacrylic acid residues as acceptor units. UV–vis spectroscopy, solution electrochemistry and DFT modelling indicated that the Me2 N- residue has the most significant effect on optical and redox properties of a photosensitizer. DSSCs with the Me2 N- functionalized dye gave the highest power conversion efficiency of the series (η = 5.61%), presumably due to the better donor ability of this unit, which promotes more effective intramolecular charge transfer (ICT) characteristics. Graphical abstract: